Isolation and identification of camelpox virus - Marodami, V; Nagendrakumar, S B; Tanwar, V K; Thiagarajan, D; Reddy, G S; tanwar, R K; Srinivasan, V A (The Indian Journal of Animal Sciences, 2011)
PCR amplification of TNFR-II gene could be used as a quick diagnostic tool in laboratories to give confirmatory results of camelpox virus belonging to Orthopox group, as this method inc1ucks its high specificity and avoid propagation of virus in embryonatcd eggs or cell culture.